On the seismic vulnerability assessment of urban areas using census data: the Lisbon Metropolitan Area as a pilot study area - Xofi, Maria (2023)
This paper presents a procedure for the application of an index-based vulnerability assessment method to the seismic risk assessment of 292,978 reinforced concrete and 152,916 unreinforced masonry buildings in the Lisbon Metropolitan Area (LMA). A singular innovation of this proposed methodology is that it is tailored to be fed with data from the 2011 national population and housing Census. The vulnerability results are then combined with the seismic hazard component into a GIS tool used to map seismic risk across the LMA. The spatial representation of these results highlights the areas of different levels of vulnerability and risk.